On time lectures on models of equilibrium - Diamond, Peter A. 1940- (Cambridge University Press, 1994)
In these two lectures, first published in 1994, Peter Diamond explores how time is modelled in theoretical analyses of individual industries and of an entire economy. In the first lecture he considers equilibrium in a single market by examining the distinction between the short run and the long run in Marshallian analysis. He proposes an explicit modelling of time in place of Marshall's use of different atemporal models for different time frames. In the second lecture he turns to models of an entire economy, and begins by considering how and why models of an entire economy should differ from models of a single industry. Both cyclical and seasonal data on the behaviour of macro-economies are examined
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Mathematisches Modell; Ökonometrisches Modell; Equilibrium (Economics) / Mathematical models; Time and economic reactions; Prices / Econometric models; Macroeconomics / Econometric models; Gleichgewichtstheorie